Cranioplasty-Autologous Bone graft Vs Titanium Mesh - Tariq Mahmood Irshad, Mahwish Jabeen, Ummara Siddique, Tahir Iqbal Mirza, Ansar Latif, Ahmed Raza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cranioplasty (CP) is a neurosurgical procedure performed after decompressive craniectomy using autologous bone graft or various artificial materials. Aim: To find differences in complications between patients who underwent CP using an autologous bone flap versus a titanium mesh as well as to identify significant risk factors for post-CP complications Study Design: Comparative cross-sectional study. Methodology: A total of 46 patients were included in this study, out of which 37 were males (80.4%) and 9 were females (19.6%). All patients underwent cranioplasty using titanium mesh or autologous bone graft. Results: Comparison of outcome between autologous graft and titanium implant was done. In 45.7% patients, autologous bone graft was used while titanium implant was used in 54.7%. 23.9% patients had developed different types of complications in both groups, out of which 81.9% were from autologous group and 18.1% belonged to titanium graft group. Surgical site infection was noted in 18.1% of patients (equally) in both groups. Craniopalsty infection was noted in 45.4% patients who underwent autologous graft. Hematoma was encountered in 2 patients; both with autologous bone graft and none in patients who had titanium mesh cranioplasty. Removal of autologous bone graft was done in one patient whileremoval was not done in the other arm of study. Bone resorption was seen in five patients, all of which had autologous bone graft. Learning curve is that this technique be followed by neurosurgeons for better outcome. Practical implicatio Titanium mesh cranioplasty is a technique to be followed by junior neurosurgeons for learning and good outcome, decrease duration of hospital stay and preservation of precious resources of hospital. Conclusion: Cranioplasty in which titanium mesh is used is superior to autologous bone grafting as it has lessercomplications. Keywords: Autologous graft, bone resorption, cranioplasty, hematoma, infection, titanium mesh.